Pembuatan Marmalade jeruk Bali (Kajian Proporsi Daging Buah : Albedo dan Penambahan Sukrosa) - ,., Jariyah; ,., Rosida; Wijayati, Dewi (REKAPANGAN, 2007)
Pembuatan Marmalade jeruk Bali (Kajian Proporsi Daging Buah : Albedo dan Penambahan Sukrosa)